Navigating the new globalization proceedings of the Fifth Annual Public Policy Conference 2019. - Annual Public Policy Conference 2016 Manila, Philippines) (Quezon City Philippine Institute for Development Studies, 2020)
The New Globalization has reached the Philippine shores. To assist the country in crafting relevant policies on this phenomenon, the fifth Annual Public Policy Conference (APPC) became the stage for a critical analysis of the issues surrounding this new phase of growth. Among others, it emphasized globalization's impact on Philippine trade, environment, public health, equity, social cohesion, and information sharing.

This volume is a compilation of the studies and papers presented during the fifth APPC. It provides government leaders, policymakers, the academe, and the public a useful reference material on the New Globalization.
UNDERSTANDING THE NEW GLOBALIZATION: -- The globotics upheaval: globalization, robotics, and the future work -- Competing in the new era of globalization -- Defending Philippine Sovereign rights in the West Philippine Sea -- WORSENING INEQUALITY: -- Global inequality trends and drivers -- Technology and inequality in Asia -- Poverty and Inequality -- What do we mean by structural change? Occupations and earnings in a village setting -- GLOBAL TRADE RESTRUCTURING: -- The trade conflict and its impact: an updated assessment -- Industrial promotion strategies amid global economic restructuring -- How technology will change global businesses and local work -- Borderless world: is the Philippines ready? -- CHALLENGES TO THE PROVISION OF GLOBAL PUBLIC GOODS : -- Financing global public goods for health: how can we make the case -- 110 million solutions to health -- The national climate change action plan and global public goods: leveraging national opportunities for sustainable development -- Regional public goods and the blue economy -- Between norm and whims: international law as a global public good -- WEAKENING SOCIAL COHESION AND TRUST: -- Disinformation producers as ordinary digital workers: behind the scenes of the Philippines' fake news industry -- How blockchain applications can improve trust in Public sector institutions
Keywords: Globalization -- Philippines -- Congresses; Technological innovations; Information society; Knowledge economy